Substitution of sesame seeds and sesame seed flour for making calcium source high phosphorus milky pie for pregnant women - Ulfah Nurida Rahmah; Mira Sofyaningsih (ARGIPA (Arsip Gizi dan Pangan), 2020)
Maternal Mortality Rate (MMR) is one indicator of community welfare in a country. One of the direct causes of maternal death is hypertension by 27.1%, with risk factors, including the imbalance of calcium. Calcium and phosphorus have a synergistic relationship. One of the food ingredients that contain calcium and phosphorus is sesame seeds, and the product was milky pie. The purpose of this study was to formulate sesame seeds and sesame seed flour to produce milky pie, a source of calcium and high phosphorus that is favored by panelists. Milky pie can be said to be a source of calcium and high phosphorus if it reaches an ALG of 195 mg of calcium and 210 mg of phosphorus. This study uses a completely randomized design (CRD). The treatment in this study was substituting wheat flour with the addition of 3 levels of sesame seeds flour (10%, 15%, and 20%), and substitution of sesame seeds by 1 level (20%). Data obtained from organoleptic tests will be analyzed statistically with ANOVA and followed by Duncan's Multiple Test with a significance level of 95%. The results showed that the addition of sesame seeds and sesame seed flour influenced the quality and level of overall panelist preference, but not at the preferred level of the taste of milky pie. The selected product is formula 3 with the substitution of wheat flour : sesame seed flour : sesame seeds equal to 60% : 20% : 20%. The serving of milky pie is and 90 g and has an energy content of 170 kcal, calcium 99 mg, and phosphorus 90 mg.